Hamstring injury prevention practices in elite sport: Evidence for eccentric strength vs. lumbo-pelvic training - Shield, A. J.; Bourne, M. N. (Sports Medicine, 2018)
Hamstring strain injuries are endemic in running-based sports. Given the economic and performance implications of these injuries, a significant body of research has emerged in recent years in an attempt to identify risk factors and develop or optimise injury prevention strategies. Surveys of injury prevention practices among medical and conditioning staff in elite sport suggest that many sporting clubs invest significant efforts in eccentric hamstring conditioning and lumbo-pelvic or trunk stability programmes. The purpose of this narrative review was to critically evaluate the evidence underpinning these practices. Single-exercise eccentric training interventions have proven effective in the prevention of primary and recurrent hamstring strains, when compliance is adequate. However, despite its almost universal acceptance, the authors are aware of only one, very recent, prospective risk factor study examining the effect of lumbo-pelvic motion during sprinting on hamstring injury risk. Furthermore, the interventions exploring the effect of lumbo-pelvic training on hamstring injury rates have not measured stability in any way. An improved understanding of the evidence underpinning commonly employed hamstring injury prevention practices may enable clinicians and coaches to better prioritise effective strategies in the increasingly complex environment of elite sport. Abstract from author